A characteristic of the species composition of pathogenic fungi of the genus Fusarium in corn biocenoses of the Voronezh region - T. M. Kolomiets; M. I. Kiseleva; N. S. Zhemchuzhina; L. F. Pankratova; S. A. Elizarova (Вавиловский журнал генетики и селекции)
Corn is one of the main crops of modern world agriculture. It ranks f irst in terms of gross grain harvests and second in terms of acreage, ceding only to the main grain crop of the globe, wheat. The problem of increasing the production of grain and green mass of corn remains one of the urgent tasks of agricultural production. High potential yields very often remain untapped due to diseases, direct losses from which are estimated at 20–50 %. The purpose of this work was to study the species composition of micromycetes on corn collected in different phases of vegetation in May-July 2020 in the Voronezh region, to identify phytopathogenic genus Fusarium fungi, to study pathogenic and phytotoxic strains of the fungi to replenish the collection of the All-Russian Scientific Research Institute of a Phytopathology. Preservation of infectious material of fungi from the genus Fusarium is of no small importance for phytopathological, immunological, breeding, genetic and toxicological studies. As a result of the mycological studies carried out, a lot of fungi isolates from the genera Fusarium, Aspergillus, Cladosporium, Curvularia, Penicillium, Rhizopus, Periconia, Pythium, Trichothecium, etc., isolated from the affected roots, stems and ears of corn in the Voronezh region in 2020 were identif ied. Fungi isolates from seven taxonomic groups: Fusarium fujikuroi Nirenberg (F. moniliforme, F. verticillioides), Fusarium oxysporum Schltdl., Fusarium culmorum (Wm.G. Sm.) Sacc., Fusarium graminearum Schwabe, Fusarium heterosporum Nees & T. Nees (F. lolii ), Fusarium roseum Link (F. sambucinum), Fusarium sporotrichioides Sherb. were tested for pathogenicity and phytotoxicity on seedlings of plant-testers. It has been shown that pathogenic and phytotoxic activity in fungi varies signif icantly between Fusarium species and within the same species. The greatest danger to corn is represented by the species F. sporotrichioides, F. graminearum, F. culmorum, F. fujikuroi, F. oxysporum, F. heterosporum, which have a high intensity of phytotoxic activity associated with the fact that they contribute to the synthesis and accumulation of dangerous toxins in plant tissues. As a result of the conducted studies, 55 strains of fungi from the genus Fusarium belonging to seven species were selected. The isolates, stable in morphological and cultural characteristics and studied for pathogenicity and toxicity, were placed for long-term storage in the Russian State Collection of Plant Pathogenic Microorganisms and Cultivars for Identif ication of Phytopathogenic Microbial Strains at the All-Russian Scientif ic Research Institute of a Phytopathology.